Achieving sustainable development goals through a sharing economy: Empirical evidence from developing economies - Yu-Te Tu; Ahmad Aljumah; Sang Van Nguyen; Cheng-Feng Cheng; Tran Duc Tai; Ranfeng Qiu (Journal of Innovation & Knowledge (JIK), 2023)
Achieving sustainable development goals (SDGs) through a sharing economy is a global concern which requires policymakers and researchers' attention. The improvement of sharing economy activities may increase sustainable development in developing economies. Thus, this study empirically examines the impact of sharing economy activities such as corporate social responsibilities (CSR), eco-design, supplier green management (SGM), internal green management (IGM), and customer green management (CGM) in achieving SDGs using data from the Emerging Seven (E7) countries. This study uses a questionnaire method to gather data from respondents and Amos software to test the validity and reliability of the data, and the relationships among the variables. The results show that SGM, eco-design, CSR, CGM, and IGM play positive roles in achieving SDGs in E7 economies. The present research provides guidelines for regulators and policymakers devising rules associated with SDGs attainment using sharing economy platforms.
Keywords: M14; Q01; Q56; 650; Corporate social responsibilities; Eco-design; Green management; Internal green management; SDGs; Sharing economy